The Necessity of Remembering Injustice and Suffering: History, Memory, and the Representation of the Romani Holocaust in Austrian Contemporary Literature - Roxane Riegler (Studies in 20th & 21st Century Literature, 2007)
This essay focuses on the role of memory in Austria. It demonstrates the significance of literary production when addressing and coming to terms with the past. Reflecting on the role of memory in history and literature, I see the boundaries between the two blurring. My inquiry includes several questions: Why should we remember? How can we integrate literature into a theoretical framework of memory and history? Why do authors take the trouble to reconstruct a burdened past or even relive pain and suffering? How do authors address the connections between the past and the present? Is it important to draw distinctions between Non-Romani and Romani authors? In my choice of texts I decided on a broad literary approach to the genocide: two autobiographies by author Ceija Stojka, which convey an inside look at individual and collective authentic Romani experience; the novels Herzfleischentartung by L. Laher and Farewell Sidonia by Erich Hackl, which are concerned with the response of the general population to the genocide; and Elfriede Jelinek's play Stecken, Stab und Stangl unmasking the denial of guilt or at least shame in present-day Austria.
Keywords: Austria; memory; remembering; past; comming to terms with the past; Non-Romani; Romani; present; genocide; Ceija Stojka; Romani experience; Herzfleischentartung; L. Laher; Farewell Sidonia; Erich Hackl; Elfriede Jelinek' s; Stecken; Stab und Stangl; Literature; play; guilt; Austrian Literature